Studi Prilaku Pasar Tanah di Daerah Pemekaran Provinsi Sulawesi Utara - maramis, joubert barens (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The result of this research shows that the buyer charactheristics and seller is effect on land price. From the supply side (seller) of the land and the demand side (buyer) of the land is create a behaviorin land market in autonomous region of North Sulawesi. The land price is significantly effect on land future price expactation. Topography of the land has effect on land price on both sides. Land distance or acces has effect on land price on both sides. Richness is the only one variable that effect on land price expactation on both sides. The crop has no significant effect on both sides. Education and earning has no effect significantly on land price expectation.Keywords: Land Market Behavior, Autonomous region, North Sulawesi